Content validity of the Recap of atopic eczema (RECAP) instrument in Dutch, English and German to measure eczema control in young people with atopic eczema: a cognitive interview study. (19th August 2022) - Gabes, Michaela; Ragamin, Aviël; Baker, Arabella; Kann, Gesina; Donhauser, Theresa; Gabes, Daniela; Howells, Laura; Thomas, Kim S.; Oosterhaven, Jart A.F.; Pasmans, Suzanne G.M.A.; Schuttelaar, Marie L.; Apfelbacher, Christian
Abstract: Background: Recap of atopic eczema (RECAP) is a patient‐reported outcome measure assessing eczema control. This instrument has been developed and validated in the UK. There are self‐reported and proxy‐reported versions in English, Dutch and German. However, it is unclear whether the self‐reported version shows adequate content validity when completed by young people (8–16 years) in these languages. Objectives: To assess the content validity (comprehensibility, relevance and comprehensiveness) of the English, German and Dutch versions of the self‐reported RECAP in young people with atopic eczema and to identify the most appropriate age cutoff for self‐completion. Methods: We conducted 23 semistructured cognitive interviews with young people aged 8–16 years, using the 'think‐aloud' method. In Germany and the Netherlands, participants were recruited in dermatology clinics and in the UK through social media and existing mailing lists. Interviews were audio recorded, transcribed verbatim and analysed in the three languages, using a problem‐focused coding manual. Transcripts were coded by two independent reviewers in each country. Themes were translated into English and compared across the three countries. Results: Significant age‐related comprehensibility issues with the last three items of the questionnaire occurred with young people aged 8–11 years, causing difficulties completing RECAP without help. However, older children had only minor problems and were able to complete the questionnaire by themselves. The self‐reported version of RECAP has sufficient content validity for self‐completion in young people aged 12 years and above. However, the German version with some translational adaptations may be appropriate for children from the age of 8 years. There may be some situations where the proxy version is needed for older children too. Conclusions: The self‐reported version of RECAP is appropriate for use from the age of 12 years. The proxy version can be used in children younger than 12 years. Other measurement properties should be further investigated. What is already known about this topic? Recap of atopic eczema (RECAP) is an instrument recommended by the Harmonising Outcome Measures for Eczema initiative for the core outcome domain of long‐term control of atopic eczema. Content validity of RECAP for self‐completion by adults and of the proxy version has been assessed. What does this study add? In this study, content validity (comprehensibility, relevance and comprehensiveness) of the self‐reported version of RECAP among young people (aged 8–16 years) with atopic eczema across the UK, Germany and the Netherlands is assessed. Based on these findings, key recommendations on how to measure eczema control in young people with atopic eczema are formulated. What are the clinical implications of this work? The Dutch, English and German self‐completion versions of RECAP are recommended for use in adolescents from the age of 12 years. The proxy version could be used in children younger than 12 years or where children are cognitively or physically incapable of reporting their experience of eczema control. Caregivers should be encouraged to complete RECAP together with their child where possible.